Development Of Indonesian Culture-Based Mathematics Learning E-Comics Integrated With Imam Syafi’i’s Educational Values To Improve Students’ Mathematical Problem-Solving Ability - Putri, Jihan Hidayah; Lubis, Ulfa Annisa; Yusnika, Yusnika; Aurellia, Clarine; Satia, Fatra (Universitas Wiralodra, 2025)
This research aims to develop a mathematics learning medium in the form of an Indonesian culture-based e-comic integrated with the educational values ​​of Imam Syafi'i on the topic of Two-Variable Linear Equation Systems (SPLDV) to improve the mathematical problem-solving skills of students at SMP IT Al Maidani. The urgency of this research is based on the low mathematical problem-solving abilities of junior high school students, as well as the lack of contextual, engaging, and Islamic character-infused learning media. The development model used was the 4D model (Define, Design, Develop, Disseminate). The research subjects consisted of 30 students in the first trial and 32 students in the second trial. Validation was conducted by media experts, material experts, religious experts, and cultural experts. The validation results indicated that the developed learning medium was valid with an average score of 4.3 (media experts), 4.2 (material experts), 4.4 (religious experts), and 4.5 (cultural experts). The first trial resulted in an increase in the average score from 76.9 (pretest) to 83.73 (posttest), with an N-Gain of 0.32 (moderate category). Based on the reflection results of the first trial, revisions were made, including improvements to the interface, the addition of sample verification questions, and additional contextual exercises. After revisions, the second trial showed a significant increase, with an average score from 77.4 to 94.25 and an N-Gain of 0.78 (high category). A total of 87.5% of students achieved classical learning completion. The results of the study demonstrate that the developed e-comic media is valid, practical, and effective in improving students' mathematical problem-solving skills and instilling Islamic character values ​​aligned with the educational values ​​of Imam Syafi'i.